(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This paper presents a novel approach to enhance the efficiency and performance of photovoltaic (PV)-water pumping systems by integrating a linear induction motor (LIM) with a double-acting reciprocating pump (DARP). The proposed system is designed to achieve direct linear motion without needing a gearbox, thereby reducing costs and improving overall efficiency. This study presents the equivalent circuit of the LIM, including the phenomena of end effects, which increases its complexity and makes control difficult. A field-oriented control (FOC) technique is suggested to achieve better motor efficiency and dynamic performance to overcome this issue. Besides, the model of PV cells in environmental conditions, such as solar irradiance and temperature, significantly influence the I-V characteristics of PV panels. The MPPT-based P&O method was implemented to maximize their output power. The simulation results checked and validated in the Matlab/Simulink software tool demonstrate that combining LIM motors with DARP pumps offers advantages over traditional rotary motor-centrifugal pumps. This confirms that it is a beneficial solution for cost-effective, eco-friendly, and efficient irrigation.